A Cost Variation Analysis of Oral Contraceptive Pills available in the Indian market - Chethan B (Tehran University of Medical Sciences, 2023)
Background: Oral Contraceptive Pills (OCPs) are highly effective contraceptives if used regularly and adequately, and they also have added non-contraceptive benefits. This gives way to their increasing use in recent years, which has led to the introduction of numerous brands of drugs with different costs in the Indian market. Hence the current study was conducted to analyze the cost ratio and cost variation of different brands of OCPs available in the Indian market and to compare the cost of branded and generic drugs. Materials and Methods: The cost of the drugs was obtained from the Current Index of Medical Specialties (CIMS) - 44th Year April - July 2022 and from the website https://www.mims.com/india/. The Cost Ratio (CR) and Percentage Cost Variation (CV) was calculated. The cost of generic drugs was obtained from the website http://janaushadhi.gov.in/SortingView.aspx. Results: 124 brands of various OCPs were available in the Indian market. Among all the regular OCPs available, the CR and CV were highest for Ormeloxifene 30mg at 10.19 and 919.4%, respectively, and they were lowest for Dienogest +Ethinylestradiol which comes under combined OCPs with the results of 1.007 and 0.73% respectively. The cost of all generic OCPs was lesser when compared with brand OCPs, and the difference in cost was maximum for Ulipristal. Conclusion: There is wide variation in the cost of Oral Contraceptive Pills available in the Indian market, and the cost of brand drugs is higher than their generic counterparts. Physicians have to be made aware of this price difference so that they can prescribe drugs that are more affordable to the patients to improve their adherence to the regimen.